2021
DOI: 10.3390/f12040509
|View full text |Cite
|
Sign up to set email alerts
|

Response of Temperate Forest Ecosystems under Decreased Nitrogen Deposition: Research Challenges and Opportunities

Abstract: Although past increases in emissions and atmospheric deposition of reactive nitrogen (Nr) provided the impetus for extensive research investigating the effects of excess N in terrestrial and aquatic ecosystems, the Clean Air Act and associated rules have led to decreases in emissions and deposition of oxidized N, especially in the eastern U.S., but also in other regions of the world. Thus, research in the near future must address the mechanisms and processes of recovery for impacted forests as they experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…Similar studies related to the N cycle have been conducted, mainly in coniferous forest ecosystems, since the 1970s [7][8][9][10][11]. In addition, the N biogeochemical research has been ongoing for 30 years at another North American temperate forest site (Fernow Experimental Forest) [12][13][14][15][16][17][18][19][20][21]. They have reported that soil N pools comprise a major proportion of the total N pools.…”
Section: Introductionmentioning
confidence: 82%
“…Similar studies related to the N cycle have been conducted, mainly in coniferous forest ecosystems, since the 1970s [7][8][9][10][11]. In addition, the N biogeochemical research has been ongoing for 30 years at another North American temperate forest site (Fernow Experimental Forest) [12][13][14][15][16][17][18][19][20][21]. They have reported that soil N pools comprise a major proportion of the total N pools.…”
Section: Introductionmentioning
confidence: 82%
“…Environmental regulations worldwide have exhibited a high degree of efficacy with respect to decreasing emissions of pollutants, including and especially N compounds. As a result, atmospheric deposition of N has declined over the past few decades on the global scale [8,24,40,[55][56][57][58][59].…”
Section: Efficiency Of Nitrogen Fertilizers In Forestrymentioning
confidence: 99%
“…Excessive competition between trees for nutrients, light, and water is prevented by precommercial cuts (thinning) with retention of a sufficient number of trees to secure high productivity of the site [8], while the supply of nutrients to trees is optimized by fertilization [9][10][11]. Alongside many other factors, the effect of fertilization on tree species depends on the content of nutrients in soil and on fertilizer form and dosage [6,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual models hypothesize that ecosystem response to reduced N deposition will exhibit a hysteretic model of recovery, in which the time from when atmospheric N deposition is reduced and ecosystem-level changes are detectable (i.e., lag-time) will be different for different ecosystem pools and fluxes 23,24 . Here, we assess the initial recovery of the terrestrial C sink that was supported under high rates of anthropogenic N deposition.…”
Section: Introductionmentioning
confidence: 99%